Le calamità ambientali nel tardo medioevo europeo: realtà, percezioni, reazioni - Matheus, Michael; Pinto, Giuliano; PICCINNI, GABRIELLA; Varanini, Gian Maria (Centro di Studi sulla Civiltà del Tardo Medioevo San Miniato, 2010)
For some time historiography has set itself the objective of studying the ways in which European society in the late Middle Ages and the early Modern Age has related to environmental disasters, addressing the perceptions and the reactions, the strategies implemented by the governments, and the repercussions on the religious mentality. In this way it has identified a sphere of investigation that is an authentic multi-disciplinary and inter-disciplinary workshop, engaging historians of institutions, culture and mentality. At the conference held in San Miniato, Italian and European historians compared notes on this subject, addressing it from different points of view and taking into consideration different environmental contexts (the cities and the rivers, the mountain, the sea, Italy, France, Holland, etc.) and different viewpoints (those of the governments, the lay 'intellectuals', the men of religion, etc.).